Analisis Keunggulan Bersaing Air Minum dalam Kemasaan Merek Narmada terhadap Merek Aqua dan Netral di Kabupaten Lombok Timur: Analysis of Competitive Advantage of Narmada Brand Bottled Drinking Water Against Aqua and Netral Brands in East Lombok Regency - Muhamad Zaril Gapari (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2025)
Each company carries out various designs, even revolutions carried out in forming competitive advantages by competing in all lines of management, even to the investor factor, in order to realize quality watch products at the lowest prices. This study focuses on finding the competitive advantage of companies engaged in the bottled drinking water (AMDK) business. Specifically, the objectives formulated are to determine and analyze the assessment criteria of consumers of each brand of bottled drinking water (brands Narmada, Aqua and Neutral) for the differentiation produced as an effort to create competitive advantage and to determine the differences in the assessment of each consumer on each differentiation that exists in each brand of bottled drinking water (brands Narmada, Aqua and Neutral). This study is comparative. The analytical tool used is the Kruskal Wallis test, by first describing the findings of each respondent's assessment of the seven competitive advantage factors. The results of this study are that the highest assessment of competitive advantage was obtained by PT. Tirta Investama with the Aqua brand of AMDK product. This has implications for relatively guaranteed market control at PT. Tita Investama in the Masbagik village market, compared to other brands of AMDK. There is a significant difference in the respondents' assessment of the competitive advantage factors (product, service, personnel, channel, image, price and promotion) created by PT, Narmada Awet Muda, PT. Tirta Investama and Harum Manis company.